Effects of non‐pharmacological interventions on pain in wound patients during dressing change: A systematic review - Yanfei Ma; Yeping Li; Chunyan Wang; Yaqing Zhang; Lihui Wang; Rong Hu; Yang Yin; Fang He (Nursing Open, 2024)
Abstract Background Changes to the wound dressing frequently cause pain. Some adverse side effects of pharmacologic pain management may cause problems or even impede wound healing. There is no systematic study of non‐pharmacologic therapies for pain during wound dressing changes, despite the gradual promotion of non‐pharmacologic pain reduction methods. Objectives To give clinical wound pain management a new direction, locating and assessing non‐pharmacological interventions regarding pain brought on by wound dressing changes are necessary. Method The researchers conducted a comprehensive literature review on non‐pharmacological interventions for pain during wound dressing changes across five databases: PubMed, Web of Science, Medline, Embase, and the Cochrane Library spanning the period from January 2010 to September 2022. The evaluation of literature and data extraction was carried out independently by two researchers, and in cases of disagreement, a third researcher participated in the deliberation. To assess the risk of bias in the literature, the researchers utilised the Cochrane Handbook for Reviews of Interventions, version 5.1.0. Results In total, 951 people were involved in 11 investigations covering seven non‐pharmacological therapies. For pain triggered by dressing changes, virtual reality (VR) distraction, auditory and visual distractions, foot reflexology, religious and spiritual care, and guided imaging demonstrated partially positive effects, with hypnosis therapy and jaw relaxation perhaps having a weak effect. Conclusion The key to managing wounds is pain management. According to our review, there is some indication that non‐pharmacologic interventions can help patients feel less discomfort when having their wound dressings changed. However, the evidence supporting this view is weak. It needs to be corroborated by future research studies with multicentre and large samples. To promote and use various non‐pharmacologic interventions in the future, it is also necessary to build standardised and homogenised paths for their implementation.